Valorizing biomass waste glycerol to fuel additive at room temperature using a nanostructured WO3/Nb2O5 catalyst - Putla, Suresh Babu; Subha, P.; Swapna, Bhattu; Singh, Nittan; Sudarsanam, Putla (Catalysis Communications, 2024)
We developed a nanostructured catalyst consisting of WO3 nanoparticles and Nb2O5 nanorods for efficient glycerol acetalization to produce a fuel additive (solketal) at room temperature. Particularly, the WO3/Nb2O5 nanocatalyst calcined at 400 degrees C (WO3/Nb2O5-4) contains W5+ species and optimum acid sites, which enhanced glycerol conversion (92.3%) with 95.6% of solketal selectivity at room temperature. The structure stability of the WO3/Nb2O5-4 catalyst during the reaction is showcased by hot-filtration study and XRD/XPS characterization. However, the inadequate regeneration of the Bronsted acid sites led to a gradual decrease in the recyclable activity of the WO3/Nb2O5-4 catalyst.
Keywords: Bronsted-Lewis acid sites; Fuel additive; Room-temperature glycerol acetalization; W5+species